Truxene Functionalized Star-Shaped Non-fullerene Acceptor With Selenium-Annulated Perylene Diimides for Efficient Organic Solar Cells - Lin, Kaiwen; Xie, Boming; Wang, Zhenfeng; Yin, Qingwu; Wang, Yuehui; Duan, Chunhui; Huang, Fei; Cao, Yong (Frontiers in Chemistry, 2021)
An electron acceptor with a truxene core and ring-fusion perylene diimide (PDI) tripolymer annulated by selenium (Se) branch, named as FTr-3PDI-Se, is designed and synthesized. FTr-3PDI-Se exhibits large conjugated planar conformation, strong absorption spectra in the regions of 300–400 and 450–550 nm, the deep HOMO energy level of 6.10 eV, and high decomposition temperature above 400℃. The FTr-3PDI-Se: PBDB-T-2Cl based device achieved a disappointing power conversion efficiency (PCE) of 1.6% together with a high Voc of 1.12 V. The low PCE was due to the large aggregates of blend film, the imbalanced hole/electron transport and low PL quenching efficiencies. The high Voc can be attributed to the high-lying LUMO level of FTr-3PDI-Se and the low-lying HOMO level of PBDB-T-2Cl. Our research presents an interesting and effective molecule-designing method to develop non-fullerene acceptor.